Liquid Metaphor in Becoming Animal by David Abram: A Transmodern Perspective Entangled with Phenomenological Insights - Walek, Agata (American & British Studies Annual, 2024)
Becoming Animal (2010) by David Abram represents a significant contribution to eco-phenomenological literature. The work describes how, by focusing on the aspect of becoming animal, i.e., tuning our senses to the pulse of the Earth, we can become fully human. The main point of the present paper is to explore the figurative language so abundantly used by the author to determine how it can play a part in opening our senses and helping us to engage with extra-linguistic reality. One recurring theme in the work is interbeing and the fluidity among all participants, a premise which influenced the selection of transmodern concepts as one of my analytical approaches. My examination of figuration is supported by conceptual metaphor theory enriched by the embodied phenomenology of Maurice Merleau-Ponty and his descriptions of how the body plays a crucial role in the creation of metaphorical expressions. The exploration of imagery reveals that metaphor exhibits not only transmodern movement across signs and extra-linguistic reality but is liquid in itself, featuring the potential for free, spirited reversibility, as well as oscillation between metaphorical analogy and literal meaning.